The Effect of Counseling on Mothers Knowledge And Attitudes About Preventing DBD In Children In The Working Area of Poasia Health Center - Ryaasti Zalzabila Ramadan; Wa Ode Sitti Asfiah Udu; Arimaswati (MEDULA: Jurnal Ilmiah Fakultas Kedokteran Universitas Halu Oleo, 2025)
ABSTRACT Background. Dengue Hemorrhagic Fever (DHF) is an infectious disease caused by a virus dengue. Poasia Health Center is one of the health centers with the most dengue fever cases. The most patiens occur at ages 4-16 years. DHF cases that occur in children can be caused a lack of knowledge and preventive attitudes carried out within the family. The aim of this research is to determine the effect of counseling on mothers' knowledge and attitudes regarding preventing dengue fever in children in the Poasia Health Center working area. Method. This research is Quasi-Eksperiment with design Without Control Groups Pretest-Posttest Design which was carried out in the Poasia Community Health Center working area. The independent variable being dengue prevention counseling while the dependent variable is the mother's knowledge and attitude. The number of samples in this study is 143 people. Data on maternal knowledge and attitudes were collect using a questionnaire and then analyze using the Wilcoxon test. Results. The dominant age was 20-30 years old with a total of 91 people with a percentage of 63.6% and the dominant last education was high school/equivalent with a total of 53 people with a percentage of 37.1%. A total of 143 respondents experienced an increase in knowledge after the counseling intervention and an increase in attitudes for 140 respondents. The results of testing knowledge and attitude data using the Wilcoxon test showed a value of p= 0.000 (p<0.05). Conclusion. There is an influence of counseling on mothers' knowledge and attitudes regarding preventing dengue fever in children in the Poasia Health Center working area. Keywords: Mother, Dengue Hemorrhagic Fever, Counseling, Knowledge, Attitude